(untitled) (Semiárida, 2021)
The Trenque Lauquen sewage treatment plant was created in 1992 when the population was substantially smaller. The objective was to determine its retention efficiency since its effluents could cause a strong negative impact on the environment. To evaluate the efficiency under extreme temperature conditions, samples of total suspended solids (TSS), chlorophyll, and total nitrogen (TN) and phosphorus (TP) were taken throughout the plant in winter and summer. The Imhoff well retained 2437 % TSS and always retained 100 % of the inorganic suspended solids. Although the plant retained between 1120 % TN and 1117 % TP, the plant discharge values (2341 mgNT/L and 3.94.1 mgPT/L) still exceed the law allowance. Variations in retention between contrasting seasons were mainly due to an increase in biological activity in summer. Retention efficiency could be improved by the use of phytoremediation, plant maintenance and expansion of existing facilities.